The 'Twofold Investment Trap': Children and their Role in Sustainable Graduation. (March 2015) - Roelen, Keetie
Abstract Despite the overall aim of graduation to lift people out of poverty in the long term, programmes remain largely focused on achieving short‐ to medium‐term change. This article postulates that graduation programmes should be more aspirational as graduation can only be truly sustainable when it is an intergenerational process. This requires greater consideration of the role of children in graduation programmes as households with children face an inter‐temporal decision‐making dilemma that places them in a 'twofold investment trap'; households are required to manage resources available from (1) adult household members and (2) children, and seek an optimal allocation of resources between investments in livelihoods and in child wellbeing. Available evidence shows that this is an almost impossible balancing act. This article proposes conceptual and programmatic considerations to ensure that graduation programmes take full account of the situation of households with children and thereby work towards sustainable and intergenerational graduation.